A scoring system categorizing risk factors to evaluate the need for ventriculoperitoneal shunt in pediatric patients after brain tumor resection - Guo, Zhong-Yin; Zhong, Zi-An; Peng, Peng; Liu, Yang; Chen, Feng (Frontiers in Oncology, 2023)
Objectives: To develop a scoring system based on independent predictors of the need for ventriculoperitoneal (VP) shunt after brain tumor resection in pediatric patients.: A total of 416 pediatric patients (≤ 14 years old) with brain tumors who underwent surgery were randomly assigned to the training (n = 333) and validation cohorts (n = 83). Based on the implementation of VP shunt, the training cohort was divided into the VP shunt group (n = 35) and the non-VP shunt group (n = 298).Univariate and multivariate logistic analyses were performed. A scoring system was developed based on clinical characteristics and operative data, and scores and corresponding risks were calculated.Results: Age < 3 (p = 0.010, odds ratio [OR] = 3.162), blood loss (BL) (p = 0.005, OR = 1.300), midline tumor location (p < 0.001, OR = 5.750), preoperative hydrocephalus (p = 0.001, OR = 7.044), and total resection (p = 0.025, OR = 0.284) were identified as independent predictors. The area under the curve (AUC) of the scoring system was higher than those of age < 3, BL, midline tumor location, preoperative hydrocephalus, and total resection (0.859 vs. 0.598, 0.717, 0.725, 0.705, and 0.555, respectively; p < 0.001). Furthermore, the scoring system showed good performance in the validation cohort (AUC = 0.971). The cutoff value for predictive scores was 5.5 points, which categorized patients into low risk (0-5 points) and high risk (6-14 points) groups.Conclusions: Our scoring system, integrating age < 3, BL, midline tumor location, preoperative hydrocephalus, and total resection, provides a practical evaluation. Scores ranging from 6 to 14 points indicate high risk.